Electron microscopic study of liver tissue from 30 thalassemic patients. - K. Thakerngpol (2018)
Electron microscopic study of liver tissue from 30 thal patients in advanced stages has been described. In all cases, regardless of the type of hemoglobin, electron microscopic observations gave identical results. Significant findings are ferroacidophilic bodies, ferroacidophilic degeneration of hepatocytes, interhepatocyte collagen, hemosiderin and ferritin, paracrystalline accumulations of ferritin molecules, and liver cell ballooning. The ultrastructures of FAB, FAD, and balloon cells were similar to those seen in viral hepatitis, but no viral particles were found.